Analisis Penguasaan TPACK Mahasiswa Pendidikan Teknik Elektro sebagai Calon Guru Abad 21 - Nur Asyifah; Hansi Effendi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
The rapid development of technology demands that prospective teachers master integrating technology, pedagogy, and content knowledge (TPACK). This study aims to analyze TPACK mastery among Electrical Engineering Education students as prospective 21st-century teachers. Using a quantitative descriptive method, data were collected from 74 students who had completed or were undergoing Teaching Field Practice (PLK) through a validated and reliable questionnaire. The results indicate that students' mastery is in the Good to Very Good category across the seven TPACK components. Specifically, Technological Knowledge (TK), Content Knowledge (CK), Technological Content Knowledge (TCK), and Technological Pedagogical Knowledge (TPK) were in the Very Good category. In contrast, Pedagogical Knowledge (PK), Pedagogical Content Knowledge (PCK), and the integrated TPACK fell into the Good category. This shows that while students possess strong technological and content competencies, the integration of these aspects with pedagogical strategies to create comprehensive and effective learning experiences still requires development. Therefore, enhancing pedagogical understanding is essential to develop vocational teacher candidates who are innovative and adaptable to advancements in educational technology.